Should formula for infants provide arachidonic acid along with DHA? A position paper of the European Academy of Paediatrics and the Child Health Foundation. Issue 1 (26th October 2019) - Koletzko, Berthold; Bergmann, Karin; Brenna, J Thomas; Calder, Philip C; Campoy, Cristina; Clandinin, M Tom; Colombo, John; Daly, Mandy; Decsi, Tamás; Demmelmair, Hans; Domellöf, Magnus; FidlerMis, Nataša; et al.
ABSTRACT: Recently adopted regulatory standards on infant and follow-on formula for the European Union stipulate that from February 2020 onwards, all such products marketed in the European Union must contain 20–50 mg omega-3 DHA (22:6n–3) per 100 kcal, which is equivalent to about 0.5–1% of fatty acids (FAs) and thus higher than typically found in human milk and current infant formula products, without the need to also include ω-6 arachidonic acid (AA; 20:4n–6). This novel concept of infant formula composition has given rise to concern and controversy because there is no accountable evidence on its suitability and safety in healthy infants. Therefore, international experts in the field of infant nutrition were invited to review the state of scientific research on DHA and AA, and to discuss the questions arising from the new European regulatory standards. Based on the available information, we recommend that infant and follow-on formula should provide both DHA and AA. The DHA should equal at least the mean content in human milk globally (0.3% of FAs) but preferably reach 0.5% of FAs. Although optimal AA intake amounts remain to be defined, we strongly recommend that AA should be provided along with DHA. At amounts of DHA in infant formula up to ∼0.64%, AA contents should at least equal the DHA contents. Further well-designed clinical studies should evaluate the optimal intakes of DHA and AA in infants at different ages based on relevant outcomes.